Diabetes gestacional en embarazada de 38 semanas de gestación del Hospital Alfredo Noboa Montenegro - Veliz Aguilera, Triccia Viviana (2019)
Gestational Diabetes is one of the most frequent metabolic disorders, defined as any carbohydrate intolerance diagnosed during pregnancy. Any alteration of glycemia that affects pregnancy should be recognized in a timely manner, reducing complications of the mother-child binomial, whether immediate or long-term, the timely diagnosis allows the obstetrician to evaluate the case and give the corresponding treatment to prevent growth. Excessive product. The present work is based on the study of the clinical case of a 35-year-old multi-patient patient who is pregnant for 38 weeks by the date of last menstruation which was referred by the Echeandia health center for presenting apparent labor, a patient with a history of diabetes Gestational pregnancy in previous pregnancy and caesarean section by fetal macrosomia 3 years ago the patient reported abdominal contraction-type pain, accompanied by polydipsia, increased urination, thirst, blurred vision, maternal overweight patient treated with Metformin in pregnancy. Once the diagnosis of Gestational Diabetes is established, close perinatal surveillance should be performed, since the objective of the diagnosis is to avoid or reduce maternal-fetal morbidity and mortality related to this condition. A decision must be made to induce labor according to gestational age, estimated fetal weight, maternal glycemic control, future research is needed to make a better diagnosis, control and treatment of Gestational Diabetes, in terms of criteria in Pregnancy care and prevention of long-term metabolic consequences for the mother and child.